2022
DOI: 10.1200/jco.2022.40.16_suppl.3520
|View full text |Cite
|
Sign up to set email alerts
|

Phase 2 study of anti-EGFR rechallenge therapy with panitumumab with or without trametinib in advanced colorectal cancer.

Abstract: 3520 Background: In RAS/RAF WT colorectal cancer (CRC), rechallenge with anti-EGFR therapy (EGFRi) in patients (pts) with prior response leads to clinical benefit, with response rates up to 30% in prior trials. However, secondary MTs in the MAPK signaling pathway have been implicated in resistance to EGFRi. We designed a phase 2 trial to evaluate the efficacy of EGFRi rechallenge +/- a MEK inhibitor (trametinib) based on pre-treatment ctDNA MTs. Methods: This trial evaluated the efficacy and safety of EGFRi r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 0 publications
0
12
0
Order By: Relevance
“…Previously, a retrospective study demonstrated a nonsignificant but clear trend that prior responders with longer interval lengths were more likely to respond to anti‐EGFR retreatment 23 . Recently, Parseghian et al also reported that patients who responded to panitumumab as an anti‐EGFR rechallenge therapy had a longer median interval from prior anti‐EGFR therapy than those nonresponders 4 . In the PURSUIT study, 5 rechallenge with panitumumab and irinotecan resulted in a higher confirmed ORR of 37.5% in patients with a longer anti‐EGFR‐free interval (>365 days) than in those with a shorter interval (<365 days, ORR: 9.5%, P = .0037).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previously, a retrospective study demonstrated a nonsignificant but clear trend that prior responders with longer interval lengths were more likely to respond to anti‐EGFR retreatment 23 . Recently, Parseghian et al also reported that patients who responded to panitumumab as an anti‐EGFR rechallenge therapy had a longer median interval from prior anti‐EGFR therapy than those nonresponders 4 . In the PURSUIT study, 5 rechallenge with panitumumab and irinotecan resulted in a higher confirmed ORR of 37.5% in patients with a longer anti‐EGFR‐free interval (>365 days) than in those with a shorter interval (<365 days, ORR: 9.5%, P = .0037).…”
Section: Discussionmentioning
confidence: 99%
“…23 Recently, Parseghian et al also reported that patients who responded to panitumumab as an anti-EGFR rechallenge therapy had a longer median interval from prior anti-EGFR therapy than those nonresponders. 4 In the PURSUIT study, 5 rechallenge with panitumumab and irinotecan resulted in a higher confirmed ORR of 37.5% in patients with a longer anti-EGFR-free interval (>365 days) than in those with a T A B L E 3 Treatment-related adverse events (TRAEs). In addition to efficacy, toxicity is the most important factor in choosing third-line or later-line therapies.…”
Section: Safetymentioning
confidence: 99%
See 1 more Smart Citation
“…However, data from two additional prospective studies presented at the 2022 ASCO Meeting reported a less-than-expected ORR of 15% and 20% for blood-based rechallenge with anti-EGFR therapy, even in patients without any acquired resistance mutations. 24,25 More interestingly, recently available data looked at the optimal timing for EGFR-directed rechallenge, suggesting that eight months (corresponding to two half-lives) could reasonably be the best time for reintroducing this treatment strategy in the path of RAS-wild-type mCRC. 16 In our study, the patient population was consistent with the standard population of pretreated mCRC since all patients were exposed to both oxaliplatin and irinotecan in previous lines.…”
Section: Discussionmentioning
confidence: 99%
“…ctDNA may rapidly identify these alterations and allow strategies of “enhanced rechallenge” encompassing not only EGFR blockade but also the prevention or treatment of the escaping refractory clones. This approach was recently investigated by Parseghian and colleagues by adopting a vertical double blockade with EGFR and MEK inhibitors ( 73 ). In this study, rechallenge with panitumumab monotherapy or panitumumab-trametinib was provided according to ctDNA status for RAS , BRAF or MAP2K1 mutant clones.…”
Section: Longitudinal Ctdna Monitoring To Detect and Trade Off Acquir...mentioning
confidence: 99%